Precision medicine and cardiac troponin biomarkers: new practice recommendations advance diagnostic precision - Lyon, Andrew W.; Lyon, Martha E. (Journal of Laboratory and Precision Medicine, 2018)
A review of the historic use of cardiac biomarkers for evaluation of coronary syndromes creates a twisting network of timelines and advances that illustrate the scientific method of precision medicine. Publication of clinical practice guidelines have established milestones along those timelines and the recent consensus recommendations for use of cardiac troponins (cTn) (1) exists in the context of previous accomplishments and the challenges ahead.